Five Paths for the Promotion, Animation and Mediation of Reading in Colombia - Blanco Quintero, Laura Ximena; Universidad Pedagógica y Tecnológica de Colombia; Rodríguez Valderrama, Jony Alexander; Universidad Pedagógica y Tecnológica de Colombia; Serrano Archila, Johanna Catalina; Universidad Pedagógica y Tecnológica de Colombia; Cetina Fuquen, Yenny Lorena; Universidad Pedagógica y Tecnológica de Colombia; Becerra Mayorga, Witton ; Universidad Pedagógica y Tecnológica de Colombia; Becerra Chirivi, Edith Mariana; Universidad Pedagógica y Tecnológica de Colombia; Castañeda Castro, Diana Cristina; Universidad Pedagógica y Tecnológica de Colombia; Becerra Lagos, José Inocencio (UPTC Editorial, 2021)
This book consists of five chapters that study, since different perspectives, a common object of study: the promotion, animation and mediation of reading in Colombia. The first chapter presentsthree methodological tendencies observed in the workshops of projects of reading PAM. The second one develops a conceptual cartography of the studied field building the notion, categorizationand differentiation of the three concepts. The third one studies the specific case of the Capital Network of Public Libraries (Biblored, Bogotá) as axe of the paradigm change of public libraries in our country. The fourth chapter is dedicated to make a state of the art of digital reading in Colombia. Finally, the fifth chapter reflectsabout some dynamics of reading promotion of projects developed among indigenous communities.